Sociological studies of children and youth. Vol. 8 - Kinney, David A., 1960- (Oxford [UK] ; London : JAI, 2001)
The volumes in this series illustrate how social organization and private, emotional experience are different phases of the social process. They show the steps by which emotional experience is shaped by social structural, macro-level processes and how these processes are changed by experience.
"Without the parent you lose the child" : teachers' expectations and parents' (non)-involvement / Katherine Brown Rosier -- Interracial relationships and racial identity processes in an urban mother-and-child rehabilitation program / Colin H. Sacks -- The colors of the rainbow : children's racial self-classification / Sheryl R. Tynes -- The social world of male and female athletes in high school / Robert Crosnoe -- On the nature and developmental significance of adolescent romantic relationships / Peggy C. Giordano, Monica A. Longmore and Wendy D. Manning -- New skills to learn in peer groups / Manuela du Bois-Reymond ... [et al.] -- Social determinants of white youths' racial attitudes : evidence from a national survey / Tyrone A. Forman -- Between a "soft" and a "hard" place : gender identity in the schooling and job behaviors of low-income minority youth / Prudence L. Carter -- Violent events and social identity : specifying the relationship between respect and masculinity in inner-city youth violence / Deanna L. Wilkinson -- "Troublemakers", "average kids", and "better-behaved youth" : the politics of labeling in social service delivery / Sudhir A. Venkatesh -- Young citizens : the position of children in communitarian theory / Gary Alan Fine, Wendy Espeland and Dean Rojeck.
Description based on print version record.
Keywords: Children -- United States -- Social conditions -- 20th century; Youth -- United States -- Social conditions -- 20th century; Age groups: children; Age groups: adolescents; Social Science -- Children's Studies; Social Science -- Sociology -- General